Metabolic changes induced by dapagliflozin, an SGLT2 inhibitor, in Japanese patients with type 2 diabetes treated by oral anti-diabetic agents: A randomized, clinical trial. (April 2022) - Horibe, Kayo; Morino, Katsutaro; Miyazawa, Itsuko; Tanaka-Mizuno, Sachiko; Kondo, Keiko; Sato, Daisuke; Ohashi, Natsuko; Ida, Shogo; Yanagimachi, Tsuyoshi; Yoshimura, Masahiro; Itoh, Ryuta; Murata, Kiyoshi; et al.
Highlights: Dapagliflozin reduced body mass principally by reducing fat mass. Skeletal muscle mass was mostly maintained after the intervention. Intra-hepatic triglyceride content was reduced with SGLT2 inhibitor treatment. Amino acid metabolism was relatively stable under SGLT2 inhibitor treatment. Abstract: Aim: We aimed to determine whether SGLT2 inhibitor dapagliflozin treatment affects body composition and amino acid (AA) metabolism. Methods: Fifty-two overweight patients treated by oral antidiabetic agents were randomly assigned to dapagliflozin (Dapa) or a standard treatment (Con) and followed for 24 weeks. The primary outcome was the change in body mass (BM) between baseline and week 24. Body composition, intrahepatic triglyceride (IHTG) content, and plasma AA concentrations were examined as secondary outcomes. Results: The change in BM was significantly larger in the Dapa than in the Con group, with a difference in the mean change of −1.72 kg (95 %CI: −2.85, −0.59; P  = 0.004) between the groups. Total fat mass was reduced by dapagliflozin treatment, but fat-free mass was maintained. IHTG content was significantly reduced in the Dapa than in the Con ( P  = 0.033). Changes in AAs showed small differences between the groups, but only serine concentrations were significantly reduced in the Dapa. Intra-group analysis showed that positive associations were observed between changes in branched chain AA concentrations and body composition only in the Dapa. Conclusions: Dapagliflozin treatment causes a reduction in BM mainly by reducing fat mass. AA metabolism shows subtle changes with dapagliflozin treatment.